PENGARUH KOMBINASI JARAK TANAM DAN DOSIS PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L. ) VARIETAS INPARI 48 BLAS - Awaludin, Awaludin; Jaenudin, Amran; Suciaty, Tety (Agroswagati : Jurnal Agronomi, 2023)
The purpose of this study was to determine the effect of combination treatment of plant spacing and nitrogen fertilizer (Urea fertilizer and NPK fertilizer) on the growth and yield of rice varieties Inpari 48 Blas. This research was carried out from May to September 2021 in the public rice fields of Sendang Village, Karangampel District, Indramayu Regency. The experimental design used was a randomized block design (RAK) with a combination pattern: Spacing consisting of: 25 cm x 25 cm spacing, 2:1 legowo spacing (25 cm x 12.5 cm x 50 cm), and plant spacing. legowo 2:1 (25 cm x 20 cm x 50 cm), N fertilizer dose consisting of 60 kg N fertilizer (100 kg Urea fertilizer and 100 kg Phonska NPK), 90 kg N fertilizer (150 kg Urea fertilizer and Phonska NPK 150 kg) and 120 kg N fertilizer (200 kg Urea fertilizer and 200 kg Phonska NPK fertilizer). The results showed that there was a significant effect between the combination of spacing and dose of nitrogen fertilizer on all growth components and yield components of the Inpari 48 Blas variety, the best weight of milled dry grain per plot was obtained at the combination treatment of row spacing legowo 2:1 (25 cm x 20 cm x 50 cm) and a nitrogen fertilizer dose of 120 kg/ha (200 kg Urea fertilizer/ha and Phonska NPK fertilizer 200 kg/ha) which yielded 14.71 kg/plot or equivalent to 6.54 tons/ha. In addition, the best dry milled grain weight per plot was also found in the combination treatment of 2:1 row spacing legowo (25 cm x 12.5 cm x 50 cm) and a nitrogen fertilization dose of 120 kg/ha (200 kg urea fertilizer/ha and Phonska NPK 200 kg/ha) which yielded 14.61 kg/plot or equivalent to 6.49 tons/ha, there was a significant correlation between plant height, number of tillers per clump, root volume, Leaf Area Index (ILD), and rate of plant growth (LPT) with the weight of milled dry grain per plot per plot.